"After all these years" – New Zealand's quota management system at the crossroads. (June 2018) - Hersoug, Bjørn
Abstract: New Zealand has rightly been admired for a new and innovative system of fishery management (the QMS) where ITQs to commercial fishers have been granted in perpetuity. By the turn of the century, the system was seen as a model for how to get the incentives right. 15 years later, it is worthwhile considering the challenges that have not been solved. The article focusses in particular on social aspects such as the labour conditions in the charter fleet, the discard problems, the relationship between the commercial and the recreational sector, the complicated procedures involved in setting and changing TACs, the involvement of Maori in fisheries management and finally on the relationship to the aquaculture sector. The main message is that strong rights to one group (the quota owners), without sorting out the rights for the other stakeholders in the marine area, have created long-term problems, which now partly paralyses the entire QMS. This also implies some serious lessons for countries who would like to copy the QMS; the system comes with a cost.